2007
DOI: 10.1021/jf062349x
|View full text |Cite
|
Sign up to set email alerts
|

Rice Amylopectin Fine Structure Variability Affects Starch Digestion Properties

Abstract: Rice; starch; RVA; amylopectin; digestibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(107 citation statements)
references
References 24 publications
7
91
5
1
Order By: Relevance
“…Studies on cooked rice flour showed that SDS is negatively correlated to short amylopectin branches but positively correlated to intermediate and long amylopectin branches, and the opposite trends were observed for RDS [8]. Similarly, a study on cooked rice grains found that digestion rate tends to increase with the increase of the chain length of long amylose chains, and tends to decrease with the proportions of long amylose chains and long amylopectin chains [163].…”
Section: Digestibilitymentioning
confidence: 97%
“…Studies on cooked rice flour showed that SDS is negatively correlated to short amylopectin branches but positively correlated to intermediate and long amylopectin branches, and the opposite trends were observed for RDS [8]. Similarly, a study on cooked rice grains found that digestion rate tends to increase with the increase of the chain length of long amylose chains, and tends to decrease with the proportions of long amylose chains and long amylopectin chains [163].…”
Section: Digestibilitymentioning
confidence: 97%
“…Many studies have shown that the proportion and the chain length of the long chains of amylopectin have special effects on its functional properties (Benmoussa, Moldenhauer, & Hamaker, 2007;Gudmundsson & Eliasson, 1990;Han & Hamaker, 2001;Jane & Chen, 1992;Jane, Xu, Radosavljevic, & Seib, 1992;Jane et al, 1999;Kalichevsky, Orford, & Ring, 1990;Lu, Chen, & Lii, 1997;Matalanis, Campanella, & Hamaker, 2009;Miles, Morris, Orford, & Ring, 1985;Shi & Seib, 1992;Shi & Seib, 1995;Wang, White, & Pollak, 1993;Yuan, Thompson, & Boyer, 1993). A greater extent of retrogradation of waxy starches was found to be directly proportional to the mole fraction of the unit chains of DP 14-24 by Shi and Seib (1992).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that the structure of amylose affects the digestibility rate (Table 27.1). 20,21 Long-chain amylose is associated with slowly digestible starch. It is thought that much of the variation in the GI of rice is due to differences in the proportion of starch present as amylose -i.e., the amylose : amylopectin ratio.…”
Section: Gi and The Amylose Content Of Ricementioning
confidence: 99%